Ten year experience with the concomitant Maze IV procedure for atrial fibrillation. Issue 2 (4th March 2022) - François, Jules; Claus, Isabelle; Cathenis, Koen; François, Bart; Provenier, Frank; Goossens, Dominique; Ballaux, Philippe K. E. W.
Abstract: Objective: The Maze IV (M-IV) procedure is regarded as the golden standard in treatment for surgical ablation of atrial fibrillation (AF); however, long-term follow-up results are scarce. We present our institutional 10-year experience. Methods: We collected data of 117 consecutive patients who have undergone a concomitant M-IV procedure between April 2006 and April 2016. Primary endpoints are freedom of atrial arrhythmias and freedom of atrial arrhythmias off antiarrhythmic drugs (AAD). Results: Forty-seven patients (40.2%) had paroxysmal AF. Two-thirds of the procedures included mitral valve surgery. The average follow-up time per patient was 3.8 years (SD 2.8). Freedom of AF at 1 year was 79%, at 5 years freedom of AF was 69% and freedom of AF off AAD was 56%. Predictors of AF recurrence in multivariate analysis were age, preoperative pacemakers, redo cardiac surgery and in-hospital AF. Preoperative PVI ablation was found to be a protective factor. Conclusions: The long-term outcomes of the M-IV procedure are good and remain stable over the years. Results could be improved if follow-up were to be intensified and recurrences dealt with aggressively. Key question: How many patients are free from AF in a 10-year period after concomitant M-IV surgical ablation? Key findings: In the long term around 70% of patients are free of AF with an increasing need for anti-arrhythmic drugs. Take home message: Early to midterm freedom from AF after concomitant M-IV procedure is high and remains stable after 3 years.